Effect of scouring on pile performance of fixed offshore jacket structures in Malaysia - Abdullah Sani, Abdul Hadi (2022)
A large number of facilities and offshore infrastructures have exceeded their original design life. The options are either decommissioning the facilities or extending the design life to the desired timeline without compromising the safety and integrity aspects of the facilities. The aspect of ageing management is the most important factor in order to control and mitigate the degradation of facilities. Scour in general is defined as erosion of loose seabed material directly around offshore structures. It is part of the component to be considered in the life extension of the offshore facilities. Code and standard practices have suggested various recommendations for the scour depth to be adopted during the initial design stage. Over estimation on the scour depth has an impact on the pile factor of safety, pilehead displacement and pile unity check which relates to the economic perspective. Therefore, it is crucial to determine the scour depth in the design stage. This study investigated the significant impact of scour depth on the pile performance, analysed the pile performance based on the design scour against the actual scour, and established the correlation between scour effect and pile performance. Fixed offshore platforms were selected from three different regions: Peninsular Malaysia Operation (PMO), Sarawak Operation (SKO), and Sabah Operation (SBO) for this study. Structural Analysis Computer System (SACS) was employed to model the structural member of the platform and the pile foundation. Static in-place analysis with pile soil interaction was conducted for the two scour case studies (actual and designed values). Results were scrutinised to establish the relation between scour depth and pile performance. The results showed pile unity check is lower than design unity check by a maximum difference of -7.6%. Minimum pile factor safety for actual scour was increased from the design with a maximum difference of 0.31%. A difference of -27.75% between actual and design value was recorded for maximum pilehead displacement. The scour depth increased, directly proportional to the pile unity check and pilehead displacement, whereas pile factor of safety was the other way around. Scour had a significant impact on the lateral load-capacity and stiffness of the pile, led to the increase in the magnitude of bending moments along the pile shaft. The findings are significant to assist the industry, especially operators to reach the optimal design scour depth.